2017
DOI: 10.1155/2017/7841823
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Antrodia cinnamomea: The Modulation of Oxidative Stress Signaling in a Mouse Model of Alcohol‐Induced Acute Liver Injury

Abstract: In the present study, the components of A. cinnamomea (AC) mycelia were systematically analyzed. Subsequently, its hepatoprotective effects and the underlying mechanisms were explored using a mouse model of acute alcohol-induced liver injury. AC contained 25 types of fatty acid, 16 types of amino acid, 3 types of nucleotide, and 8 types of mineral. The hepatoprotective effects were observed after 2 weeks of AC treatment at doses of 75 mg/kg, 225 mg/kg, and 675 mg/kg in the mouse model. These effects were indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 57 publications
(65 reference statements)
4
37
0
Order By: Relevance
“…In agreement with previous observations in alcohol-induced liver injury [ 30 , 40 ], we found that the NF-kB pathway in the liver was activated by alcohol feeding. Activation of NF-kB has been reported to contribute to liver injury through production of pro-inflammatory cytokines [ 15 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous observations in alcohol-induced liver injury [ 30 , 40 ], we found that the NF-kB pathway in the liver was activated by alcohol feeding. Activation of NF-kB has been reported to contribute to liver injury through production of pro-inflammatory cytokines [ 15 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Alcoholic liver disease (ALD) has become an important public health issue around the world, with a death rate of 20% 1 3 . In addition, the incidence of ALD has increased in China as a consequence of an increased frequency of alcohol consumption 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, induced expression of cyclooxygenase-2 (COX-2) contributes to the inflammatory response and participates in the aggravation of alcohol-induced liver injury 18 . Moreover, nitric oxide (NO) is involved in a wide range of toxic oxidative reactions 1 , and alcohol consumption induces a significant increase in NO levels, as a result of the elevated synthesis of inducible nitric oxide synthase (iNOS) 2 . Therefore, increases in NO generation may be an early indicator of ethanol-induced liver damage, and inhibiting the release of NO is a potential method for controlling inflammation 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A. cinnamomea ameliorated liver injury by reducing necrosis, inflammatory infiltration, and cell apoptosis and downregulated cleaved caspase‐3, ‐8, and ‐9, p‐Akt and p‐NF‐ κ B expression levels in liver samples. This hepatoprotective action of A. cinnamomea was recognized by decreased oxidative stress which was correlated with Akt/NF‐ κ B signaling (Liu et al, ).…”
Section: Biological Activitiesmentioning
confidence: 99%